2006
DOI: 10.1093/ajcn/84.6.1449
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth among term children whose birth weight was appropriate for gestational age has a longer lasting effect on body fat percentage than on body mass index

Abstract: Rapid growth in infancy and early childhood results in an increased BMI and %BF throughout childhood and an increased risk of overweight at age 7 y among AGA children. Rapid growth in AGA children has a more pronounced effect on %BF than on BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 34 publications
6
61
0
5
Order By: Relevance
“…A few studies have been published after Ong and Loos's systematic review and confirm their findings. [42][43][44] One of these recent studies 42 stratified analyses by breastfeeding status and found similar association for subjects who were breast-fed compared to those who were not, suggesting that the association between rapid infancy weight gain and later development of obesity is not limited to formula-fed infants. The focus of most studies has been to investigate weight gain as changes in weight for age, because it is the best indicator of a positive energy balance.…”
Section: Statement Of Purpose and Methodsmentioning
confidence: 92%
“…A few studies have been published after Ong and Loos's systematic review and confirm their findings. [42][43][44] One of these recent studies 42 stratified analyses by breastfeeding status and found similar association for subjects who were breast-fed compared to those who were not, suggesting that the association between rapid infancy weight gain and later development of obesity is not limited to formula-fed infants. The focus of most studies has been to investigate weight gain as changes in weight for age, because it is the best indicator of a positive energy balance.…”
Section: Statement Of Purpose and Methodsmentioning
confidence: 92%
“…Nevertheless, we did not find evidence to suggest that exposure to atole during the first 1000 d was associated with BMI latent class membership. Studies in high-income countries have shown an association between rapid growth before age 2 y and obesity risk (25)(26)(27); however, others found no increased risk when weight gain was appropriate for linear growth (28,29). A study of infant BMI trajectories in the Philippines found that accelerated infant BMI did not have longterm consequences on young-adult BMI (30).…”
Section: Discussionmentioning
confidence: 99%
“…La media de EG fue de 39,1 semanas (IC 95% 38, 4). En 9% se registró el antecedente de EG menor a 37 semanas, en tanto que en 15,48% de bajo peso para la edad gestacional.…”
Section: Resultsunclassified
“…[1][2][3][4][5][6] A su vez, el bajo peso al nacer y la restricción del crecimiento guardan relación con el desarrollo de enfermedades en la edad adulta, en el cual median diferentes mecanismos, vinculados a las características de crecimiento en ese período. 6 El bajo peso para la edad gestacional, así como la restricción del crecimiento intrauterino pueden ser seguidos por un período de crecimiento acelerado.…”
Section: Introductionunclassified